Restoring brain cholesterol turnover improves autophagy and has therapeutic potential in mouse models of spinocerebellar ataxia - Nóbrega, Clévio David Rodrigues (2019)
Spinocerebellar ataxias (SCAs) are devastating neurodegenerative disorders for which no curative or preventive therapies are available. Deregulation of brain cholesterol metabolism and impaired brain cholesterol turnover have been associated with several neurodegenerative diseases. SCA3 or Machado-Joseph disease (MJD) is the most prevalent ataxia worldwide. We show that cholesterol 24-hydroxylase (CYP46A1), the key enzyme allowing efflux of brain cholesterol and activating brain cholesterol turnover, is decreased in cerebellar extracts from SCA3 patients and SCA3 mice. We investigated whether reinstating CYP46A1 expression would improve the disease phenotype of SCA3 mouse models. We show that administration of adeno-associated viral vectors encoding CYP46A1 to a lentiviral-based SCA3 mouse model reduces mutant ataxin-3 accumulation, which is a hallmark of SCA3, and preserves neuronal markers. In a transgenic SCA3 model with a severe motor phenotype we confirm that cerebellar delivery of AAVrh10-CYP46A1 is strongly neuroprotective in adult mice with established pathology. CYP46A1 significantly decreases ataxin-3 protein aggregation, alleviates motor impairments and improves SCA3-associated neuropathology. In particular, improvement in Purkinje cell number and reduction of cerebellar atrophy are observed in AAVrh10-CYP46A1-treated mice. Conversely, we show that knocking-down CYP46A1 in normal mouse brain impairs cholesterol metabolism, induces motor deficits and produces strong neurodegeneration with impairment of the endosomal-lysosomal pathway, a phenotype closely resembling that of SCA3. Remarkably, we demonstrate for the first time both in vitro, in a SCA3 cellular model, and in vivo, in mouse brain, that CYP46A1 activates autophagy, which is impaired in SCA3, leading to decreased mutant ataxin-3 deposition. More broadly, we show that the beneficial effect of CYP46A1 is also observed with mutant ataxin-2 aggregates. Altogether, our results confirm a pivotal role for CYP46A1 and brain cholesterol metabolism in neuronal function, pointing to a key contribution of the neuronal cholesterol pathway in mechanisms mediating clearance of aggregate-prone proteins. This study identifies CYP46A1 as a relevant therapeutic target not only for SCA3 but also for other SCAs.